Polygamy in Perspective of Islamic Law Hermeneutics - Danial, Danial (Institut Agama Islam Negeri Curup, 2023)
This article examines the legal verses of polygamy from a hermeneutical perspective. The third verse of surah al-Nisa is often understood as a verse commanding polygamy, because it contains recommendations to marry more than one woman, namely: two, three and four. The data used in this article are divided into two categories. The collected data were then analysed using the hermeneutic theory of Emelio Betti, Martin Heidegger, Hans Georg Gadamer and Paul Ricoeur with a descriptive method. The results of the research based on the hermeneutic theories above show that the third verse of surah al-Nisa which is usually used as the argument for polygamy from the Koran actually reinforces the recommendation of monogamy because according to Betti the purpose of marriage is sakinah mawaddah wa rahmah, this goal is difficult to realize in polygamy. Then according to Heidegger the verse above talks about justice for orphans. Furthermore Gadamer that polygamy is carried out with 2 conditions; (1) the 2nd, 3rd and 4th wives are widows who have orphans; (2) there must be a feeling of worry that they cannot do good and justice to orphans except by marrying their mothers. Finally, Ricoeur is of the view that the verse above is an order to act fairly in protecting the assets of orphans. The conclusion is that the third verse of surah al-Nisa is a recommendation for monogamy, not an order for polygamy.